42.3k views
2 votes
Solve the system of linear equations below by substitution.

y = -2x + 6

-4x - 6y = 4

Group of answer choices

(-2, 10)

(5, -4)

(3, 0)

(0, 6)

User Muffel
by
5.8k points

2 Answers

3 votes

Answer:

(5, -4)

Explanation:

Substitute y from the first equation into the second equation:

-4x - 6(-2x + 6) = 4

Simplify:

-4x + 12x - 36 = 4

8x = 40

x = 5

The only answer choice where x = 5 is (5, -4).

User Sahil Popli
by
4.8k points
3 votes

Answer:


\boxed {\boxed {\sf (5, -4)}}

Explanation:

We are given the two equations:


y= -2x+6 \\-4x-6y=4

We are asked to solve by substitution. Since we know that y is equal to -2x+6, so we can substitute the expression in for y in the second equation.


-4x-6y=4


-4x-6(-2x+6)=4

Now, solve for x by isolating the variable on one side of the equation.

First, distribute the -6 into the expression. Multiply each term in the parentheses by -6.


-4x+ (-6*-2x)+(-6*6)=4


-4x+12x+(-6*6)=4


-4x+12x-36=4

Combine like terms. There are 2 x terms that can be added.


(-4x+12x)-36=4


8x-36=4

36 is being subtracted from 8x. The inverse of subtraction is addition, so add 36 to both sides of the equation.


8x-36+36=4+36


8x=40

x is being multiplied by 8. The inverse of multiplication is division, so divide both sides by 8.


(8x)/(8) =(40)/(8)


x=5

x is known, so we can find y using the first equation.


y=-2x+6

x is equal to 5, so substitute the value in.


y=-2(5)+6

Multiply first.


y=-10+6

Add.


y=-4

A solution is written as (x,y). So, the solution to this equation is (5, -4).

User Ozgen
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.